2024
DOI: 10.3390/min14040381
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Physicochemical Characteristics of Ores on the Efficiency of Underground Well Leaching of Uranium Deposits in Kazakhstan

Kuanysh Togizov,
Zhiger Kenzhetaev,
Raushan Temirkhanova
et al.

Abstract: The features of uranium mining on Kazakhstan’s enterprises have been examined, and uranium deposits located in the Syrdarya and Shu-Sarysu depressions have been described. Actual and projected data on the development of technological blocks in areas with complex geological structures have been analyzed and compared. Core samples were collected and, using X-ray diffraction analysis, quantitative and qualitative characteristics as well as mineral compositions of ores from various productive horizons of uranium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The directions for the development and improvement of these methods can be very different. For example, in the geological direc tion, to improve the quality and completeness of mining, modern geophysical well logging methods of research are used, such as the method of radio-wave geointoscopy, which has shown high efficiency in tracking and controlling technological processes when mining uranium by ISL methods [5][6][7][8]. The geotechnological direction is focused on the use of various chemical complexes and reagents for the intensification of mining.…”
Section: Introductionmentioning
confidence: 99%
“…The directions for the development and improvement of these methods can be very different. For example, in the geological direc tion, to improve the quality and completeness of mining, modern geophysical well logging methods of research are used, such as the method of radio-wave geointoscopy, which has shown high efficiency in tracking and controlling technological processes when mining uranium by ISL methods [5][6][7][8]. The geotechnological direction is focused on the use of various chemical complexes and reagents for the intensification of mining.…”
Section: Introductionmentioning
confidence: 99%